Remediation and hypermediacy: Ezekiel's World as a case in point. (May 2020) - Kohn, Ayelet; Weissbrod, Rachel
This article deals with Kovner's graphic narrative Ezekiel's World (2015) as a case of remediation and hypermediacy. The term 'remediation' refers to adaptations which involve the transformation of the original work into another medium. While some adaptations strive to eliminate the marks of the previous medium, others highlight the interplay between different media, resulting in 'hypermediacy'. The latter approach characterizes Ezekiel's World due to its unique blend of artistic materials adapted from different media. The author, Michael Kovner, uses his paintings to depict the story of Ezekiel – an imaginary figure based on his father, the poet Abba Kovner who was one of the leaders of the Jewish resistance movement during World War II. While employing the conventions of comics and graphic narratives, the author also makes use of readymade objects such as maps and photos, simulates the works of famous artists and quotes Abba Kovner's poems. These are indirect ways of confronting the traumas of Holocaust survivors and 'the second generation'. Dealing with the Holocaust in comics and graphic narratives (as in Spiegelman's Maus: A Survivor's Tale, 1986) is no longer an innovation, nor is their use as a means to deal with trauma; what makes this graphic narrative unique is the encounter between the works of the poet and the painter, which combine to create an exceptionally complex work integrating poetry, art and graphic narration.